A Companion to British Art : 1600 to the Present. - Arnold, Dana (Blackwell companions to art history., 2013)
This companion is a collection of newly-commissioned essays written by leading scholars in the field, providing a comprehensive introduction to British art history. A generously-illustrated collection of newly-commissioned essays which provides a comprehensive introduction to the history of British artCombines original research with a survey of existing scholarship and the state of the field Touches on the whole of the history of British art, from 800-2000, with increasing attention paid to the periods after 1500Provides the first comprehensive introductio.